Low-Carbon and Environmentally Sustainable Aquaculture in Coastal Ecosystems: A Systematic Literature Review - Iman Supriatna; Ainul Alim Rahman (Indonesian Journal of Environmental Management and Sustainability, 2026)
Low-carbon aquaculture is increasingly recognized as a vital strategy to mitigate climate change, improve resource efficiency, and ensure sustainable food production. This systematic review, following the PRISMA 2020 protocol, analyzed 58 peer-reviewed studies selected from 312 published between 2020-2024, providing a transparent and replicable synthesis of the current evidence. Research is predominantly focused in Asia and Europe, regions where rapid aquaculture growth coincides with emerging climate policies. Key strategies for reducing environmental impacts include Integrated Multi-Trophic Aquaculture (IMTA), cultivation of low-trophic species such as seaweeds and filter feeders, and the restoration of coastal ecosystems, all of which enhance carbon sequestration, nutrient cycling, and ecosystem resilience. The review identifies the most commonly reported sustainability indicators as global warming potential (GWP), energy consumption, land use, nutrient loading, and eutrophication. Despite ongoing technological innovations, global aquaculture remains largely unsustainable with persistently low environmental performance. Barriers to improvement include incomplete carbon accounting, fragmented regulatory frameworks, and limited consumer awareness. Additionally, significant knowledge gaps in greenhouse gas emissions and carbon sequestration constrain robust life cycle assessments. Transitioning to low-carbon aquaculture requires not only technological innovation but also with stronger governance, ecosystem-based management, and integrated policy frameworks to enhance sustainability and climate resilience. This review underscores the urgency of coordinated action across research, industry, and policy sectors to optimize low-carbon strategies, address existing knowledge gaps, and support the development of sustainable aquaculture systems that are both environmentally responsible and economically viable.